Developing an IT-based library service model to enhance learning quality - Sukarjono Sukarjono; Sumaryanto Sumaryanto; Sumarjo Sumarjo; Sulis Triyono (Jurnal Cakrawala Pendidikan, 2026)
The rapid advancement of digital technology has transformed how students access information, yet many university libraries still struggle to provide services that meet the specific needs of specialized disciplines. This study aims to develop a library service model tailored to the specific characteristics of Sports and Health Science students. The development focuses on leveraging information technology through native applications for Android and iOS. Following a 4-D research and development (R&D) framework, data were collected using three instruments: assessments from subject matter experts, media experts, and students, complemented by in-depth interviews. Quantitative data were processed using SPSS and Microsoft Excel software. Descriptive analysis was employed to outline respondent characteristics, user satisfaction levels, and overall data distribution, while inferential statistical tests, including t-tests and ANOVA, were used to identify significant differences between respondent groups. The research resulted in an IT-based library service product that achieved a high validity score of 4.72 on a 5-point scale. Validity and reliability analysis using product-moment correlation confirmed that all questionnaire items were significantly correlated with total scores (p<0.05). Comparative analysis before and after application implementation regarding learning quality showed significant improvements. In conclusion, the implementation of this IT-based library application is effective in enhancing learning quality.